Witnesses of the stay in the Citadel, companions of exile. About things around prisoners - Załęczny, Jolanta (In the Mirror of Things, 2022)
The 10th Pavilion is a place of martyrdom of the Polish nation. It is recalled by the preserved authentic prison interiors and the items stored in them that tell the stories of prisoners and inspire reflection on the past. They were witnesses of human experiences, testimony of events, carriers of emotions. Today they complement the historical narrative. Their presentation was enriched with excerpts from the memoirs of the prisoners of the 10th Pavilion, which made them more personal.